2012
DOI: 10.1371/journal.pone.0030265
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Apoptosis by Mitochondrial Phosphatase PGAM5 in the Mushroom Body Is Crucial for Heat Shock Resistance in Drosophila melanogaster

Abstract: The heat shock (HS) response is essential for survival of all organisms. Although the machinery of the HS response has been extensively investigated at the cellular level, it is poorly understood at the level of the organism. Here, we show the crucial role of the mushroom body (MB) in the HS response in Drosophila. Null mutants of the mitochondrial phosphatase Drosophila PGAM5 (dPGAM5) exhibited increased vulnerability to HS, which was reversed by MB-specific expression of the caspase inhibitor p35, and simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…However, these phenotypes would also be explained by a loss of anterior cells (Offner et al, 2005). Necroptosis-promoting and -protective roles, as well as pro-and anti-apoptotic functions of Pgam5 have been described (Ishida et al, 2012;Lenhausen et al, 2016;Lu et al, 2016;Moriwaki et al, 2016;Zhou et al, 2012). However, we have not detected any local or global changes in cell death or apoptosis in Pgam5 morphant Xenopus embryos, indicating that regulation of cell death does not represent the major early developmental function of Pgam5 in Xenopus.…”
Section: Pgam5 Inhibits Recruitment Of Dvl2 To the Tcf1 Complexcontrasting
confidence: 57%
See 1 more Smart Citation
“…However, these phenotypes would also be explained by a loss of anterior cells (Offner et al, 2005). Necroptosis-promoting and -protective roles, as well as pro-and anti-apoptotic functions of Pgam5 have been described (Ishida et al, 2012;Lenhausen et al, 2016;Lu et al, 2016;Moriwaki et al, 2016;Zhou et al, 2012). However, we have not detected any local or global changes in cell death or apoptosis in Pgam5 morphant Xenopus embryos, indicating that regulation of cell death does not represent the major early developmental function of Pgam5 in Xenopus.…”
Section: Pgam5 Inhibits Recruitment Of Dvl2 To the Tcf1 Complexcontrasting
confidence: 57%
“…3B). Pgam5 has been functionally implicated in apoptosis, necroptosis and mitophagy, although it apparently acts as positive or negative regulator, depending on the experimental context (Chen et al, 2014;Ishida et al, 2012;Lenhausen et al, 2016;Lu et al, 2016;Moriwaki et al, 2016;Wang et al, 2012). Increased cell death in the anterior ectoderm might lead to a loss of head structures, while inhibition of cell death in early Xenopus embryos results in an expansion of neuroectoderm (Offner et al, 2005;Yeo and Gautier, 2003).…”
Section: Pgam5 Is Required For Head Induction In Xenopus Laevis Embryosmentioning
confidence: 99%
“…In addition, cleaved PGAM5 was implicated in apoptosis (31, 38). In contrast to these pro-apoptotic functions, Drosophila PGAM5 was shown to protect against heat shock-induced apoptosis of the mushroom body (39). The role of PGAM5 in necroptosis is similarly confusing.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent reports have suggested that PGAM5 is involved in multiple cell death pathways in a context-dependent manner. For example, we have recently reported that flies deficient in the Drosophila ortholog of mammalian PGAM5 (dPGAM5) are vulnerable to heat shock stress mainly because of increased apoptosis in neurons in the mushroom body, suggesting the role for PGAM5 in apoptosis regulation (41). On the other hand, dPGAM5 has recently been shown to act as an exacerbating factor for mitochondrial degeneration and dopaminergic neuronal cell death in the model of Parkinson disease induced by mutation of the Drosophila PINK1 gene (42).…”
Section: Discussionmentioning
confidence: 99%